School Disciplinary Climate and Students’ Academic Engagement as Predictors of Academic Achievement in Public Secondary Schools in Akwa Ibom State, Nigeria - Uboh, Daniel Effiong; Nkoyo, N. Thomas; Sunday, Edima Sylvanus; Itaketo, Blessing Bassford (Journal of Current Research and Studies, 2026)
Academic achievement remains a major indicator of educational effectiveness in secondary schools. However, increasing concerns about declining student performance in public secondary schools in Nigeria have raised questions about the role of school climate and student engagement in learning outcomes. This study examines school disciplinary climate and students’ academic engagement as predictors of academic achievement in public secondary schools in Akwa Ibom State, Nigeria. The study adopts a correlational research design. The population comprised Senior Secondary Two (SS2) students, from which a sample of 420 students was selected using multi-stage sampling techniques. Three instruments were used for data collection: School Disciplinary Climate Scale (SDCS), Academic Engagement Questionnaire (AEQ), and Academic Achievement Record Form (AARF). Data were analyzed using Pearson Product Moment Correlation and Multiple Regression Analysis at 0.05 level of significance. Findings are expected to reveal significant positive relationships between disciplinary climate, academic engagement, and academic achievement. The study is anticipated to establish both variables as significant predictors of students’ academic performance. It is recommended that school administrators strengthen disciplinary consistency and promote engagement-oriented classroom practices to enhance academic achievement.